Ergonomic Evaluation of Hand Operated Maize Shellers - Solanki, S N; Ramteke, R T; Kawade, S C; Gite, L P (Journal of Agricultural Engineering, 2006)
Three types of hand operated maize shellers were evaluated ergonomically. The performance in respect of cardiac cost, overall tiredness, body part discomfort and output were evaluated. The heart rate while working with all maize shellers indicates moderate workload on the subjects. The overall discomfort score varied from 3.5 to 4 i.e. more than light discomfort' and body part discomfort score was 51 for all the maize shellers. The highest output was observed with maize sheller having serrated tins than other two maize shellers. Also the use of this maize sheller could help to reduce the drudgery by 18.75 and 45.13 % than tubular and octagonal shaped maize shellers respectively having plain fins, as calculated from the heart rate data.